2021
DOI: 10.3390/jpm11010046
|View full text |Cite
|
Sign up to set email alerts
|

A Genotype-Phenotype Correlation Study of Exon Skip-Equivalent In-Frame Deletions and Exon Skip-Amenable Out-of-Frame Deletions across the DMD Gene to Simulate the Effects of Exon-Skipping Therapies: A Meta-Analysis

Abstract: Dystrophinopathies are caused by mutations in the DMD gene. Out-of-frame deletions represent most mutational events in severe Duchenne muscular dystrophy (DMD), while in-frame deletions typically lead to milder Becker muscular dystrophy (BMD). Antisense oligonucleotide-mediated exon skipping converts an out-of-frame transcript to an in-frame one, inducing a truncated but partially functional dystrophin protein. The reading frame rule, however, has many exceptions. We thus sought to simulate clinical outcomes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
(51 reference statements)
1
14
0
Order By: Relevance
“…Other factors over and above gene mutation type and dystrophin protein content of muscle contribute to variation in clinical phenotypes of both DMD and BMD, including genetic modifiers [14] and socioeconomic status [15]. Natural history studies of BMD patient cohorts have shown marked clinical variability, even between those with the same in-frame mutation, ranging from just slightly milder than DMD to asymptomatic [13,16,17]. Importantly, muscle MRI findings of the degree of fatty replacement of skeletal muscles appear more correlated with clinical symptoms than either dystrophin protein content or gene mutation [18,20].…”
Section: Becker Muscular Dystrophy and Clinical Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors over and above gene mutation type and dystrophin protein content of muscle contribute to variation in clinical phenotypes of both DMD and BMD, including genetic modifiers [14] and socioeconomic status [15]. Natural history studies of BMD patient cohorts have shown marked clinical variability, even between those with the same in-frame mutation, ranging from just slightly milder than DMD to asymptomatic [13,16,17]. Importantly, muscle MRI findings of the degree of fatty replacement of skeletal muscles appear more correlated with clinical symptoms than either dystrophin protein content or gene mutation [18,20].…”
Section: Becker Muscular Dystrophy and Clinical Variabilitymentioning
confidence: 99%
“…Splice site mutations are ‘leaky’ in that they are often non-null (some normal dystrophin) [ 12 ]. Efforts to predict the clinical outcomes of different in-frame deletions based on systematic analyses of large DNA/phenotype databases find considerable heterogeneity in observed phenotypes [ 13 ].…”
Section: Becker Muscular Dystrophy and Clinical Variabilitymentioning
confidence: 99%
“…However, even if great progress has been made during the last two decades in different subgroups of neuromuscular disorders, there are still numerous challenges to resolve, such as the optimization of therapeutic knock-down strategies [3], targeting specific muscles and/or tissues of the nervous system [1], identifying genetic modifiers that can impair a therapeutic strategy [2], targeting common pathways being affected in different patient subgroups for a given disease [4,5], or understanding the impact of neuromuscular disorders on other tissues that could be affected but may be understudied. This Special Issue, entitled "Understanding Neuromuscular Health and Disease: Advances in Genetics, Omics, and Molecular Function", encompasses some 15 publications from colleagues working on a diverse range of neuromuscular diseases, including Duchenne muscular dystrophy [6][7][8][9], facioscapulohumeral dystrophy [3,10,11], amyotrophic lateral sclerosis [4,5,12], spinal muscular atrophy [2], Emery-Dreifuss muscular dystrophy [13], and rheumatoid arthritis [14]. Looking across diseases, several themes are recurrent, such as the efforts to identify genotype-phenotype correlations in DMD [6,7,9] and ALS [4,5], the quest for effective biomarkers in many neuromuscular conditions [2,8,10,14], and the use of genomic and multi-omic approaches towards better ways to identify biomarkers and to understand disease [10,12,13].…”
mentioning
confidence: 99%
“…The search for genotype-phenotype correlations can be aimed at the improved understanding of disease [4,5,7,9], but may also be relevant to potential therapeutic outcomes [6]. Of relevance to this Special Issue are genotype-phenotype correlations in DMD [6,7,9] and in ALS [4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation